Interim Election as a Constitutional Bridge for Aceh's Legislative Vacuum after Decision No. 135/PUU-XXII/2024 - Apri Rotin Djusfi; Agung Munandar; Adella Yuana; Dara Quthni Effida; Anhar Fazri (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2026)
The Constitutional Court Decision No. 135/PUU-XXII/2024, which establishes unified concurrent local elections (Pemilu Daerah), creates a two-year legislative vacuum (2029–2031) in the Aceh House of Representatives (DPRA) and the Regency/Municipal House of Representatives (DPRK). This issue originates from a systematic domino effect caused by the fixed-term executive rule under Article 65 of the Law of Aceh Governance (UUPA) clashing with the rescheduled 2031 local electoral calendar. Therefore, this normative-doctrinal legal study aimed to reconstruct the transitional legal mechanisms governing the occupation of local legislative seats. In the process, statute, conceptual, case, and comparative methods were adopted. Brazil’s 1988 ADCT, Nepal’s 2007 Interim Constitution, and the legal mindsets of Constitutional Court Decisions No. 55/2019 and 143/2023 served as comparative legal analogies. Furthermore, data were analysed qualitatively using a prescriptive method. The results showed that Model 1 (Limited Extension) and Model 2 (Collective Parliament) contained fundamental democratic deficits, as both bypassed direct electoral mandates. Model 3 proposed institutionalising an Interim Election with a one-off shortened term leading up to the 2031 concurrent cycle and was considered the most rational and constitutional solution. This scheme is technically viable for integration into the 2029 elections, supported by the General Elections Commission (KPU) Regulation No. 10/2023 and the digital infrastructure of the Aceh Independent Election Commission (KIP). In conclusion, the Interim Election served as a solid jural bridge to safeguard popular sovereignty while fully protecting the exclusive political recruitment rights of local political parties under Article 76 of the UUPA.